Intermolecular interception of alpha-oxo gold carbenes of nitroalkyne cycloisomerization with 1, 2-benzo[d]isoxazole: synthesis of functionalized quinazoline 1-oxides - Dhote, Pawan S.; Pund, Kishor A.; Ramana, V, Chepuri (Journal of Organic Chemistry, 2021)
The known nitrogen-transfer reagent 1,2-benzo[d]isoxazole has been used to trap the postulated a-oxo gold carbene intermediate involved in the [Au]-catalyzed internal redox process of 2-alkynylnitrobenzenes. This process led us to develop a general convergent method for the synthesis of highly functionalized quinazoline 1-oxides.

Interrupting the [Au]-catalyzed nitroalkyne cycloisomerization: trapping the putative alpha-oxo gold carbene with benzo[c]isoxazole - Dhote, Pawan S.; Ramana, V, Chepuri (Organic Letters, 2021)
The [Au]-catalyzed nitroalkyne cycloisomerization of 2-alkynylnitrobenzenes leading to anthranils has been interrupted by possible trapping of the postulated intermediate alpha-oxo gold carbene with an external nucleophile such as benzo[c]isoxazole (anthranil). At the outset, this provides a simple synthesis of highly functionalized 3-acyl-(2-formylphenyl)-2H-indazoles with the sequential C-O, C-N, and N-N bond formations. This provides indirect support for the existence of alpha-oxo gold carbenes in the [Au]-catalyzed internal redox processes of nitroalkynes.